Relevance of business administration management - Roque Casimiro, Cleto Carlos (2024)
Business administration management encompasses a series of processes that guarantee the achievement of institutional goals. The objective of this research was to analyze the relevance of business administration management. A systematic review was conducted that included papers related to business administration management and study analyses relevant to the categories of business administration management, business administration management strategies, and digital administration management. The study was conducted using 22 papers published in databases such as Scopus, 5 papers; Web of Science, 2 papers; Scielo, 1 paper, and Latindex, 14 papers. The study concluded that administration management has practical relevance, allowing the establishment of organizational goals and objectives. This should be carried out efficiently, since employee dedication experiences a gradual increase and the company achieves productivity according to expectations, proposed objectives and significantly promotes a quality economy. Likewise, administration management must consider strategies such as the application of the various phases of administration processes (planning, organizing, directing, controlling), in addition to strengthening supervisory and regulatory functions; adapting administration management strategies to the local context; developing democratic participation, a culture of peace, and encouraging all civil society actors to implement changes that promote the construction of cultures that foster communication, equity, solidarity, empathy, and respect. Digital administration management attracts customers or users, so organizations must adapt to new technologies, as it not only creates competitive advantages, but also promotes sustainability and market competitiveness.